2005
DOI: 10.1210/jc.2005-0987
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Mutation Predicts a Poorer Clinical Prognosis for Papillary Thyroid Cancer

Abstract: In patients with PTC, BRAF mutation is associated with poorer clinicopathological outcomes and independently predicts recurrence. Therefore, BRAF mutation may be a useful molecular marker to assist in risk stratification for patients with PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

38
735
12
20

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 898 publications
(805 citation statements)
references
References 29 publications
38
735
12
20
Order By: Relevance
“…Additionally, the BRAF mutation occurs most commonly in aggressive subtypes of PTC [178,201]. Loss of NIS and TPO are early markers of dedifferentiation and they are also responsible for poor prognosis in BRAF positive PTCs [202].…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…Additionally, the BRAF mutation occurs most commonly in aggressive subtypes of PTC [178,201]. Loss of NIS and TPO are early markers of dedifferentiation and they are also responsible for poor prognosis in BRAF positive PTCs [202].…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…BRAF mutations are the most common mutation in PTCs, and the transverse point mutation at codon 600 ( BRAF V600E) is the most common type of BRAF mutations 15, 16, 17. Several studies demonstrated a strong association between BRAF mutations and poor clinicopathological outcomes for patients with PTCs 18, 19, 20. RAS mutations can be found in follicular neoplasms and are more common in FTCs (40–50%) than in follicular thyroid adenomas (20–40%) 21, 22, 23, 24.…”
Section: Introductionmentioning
confidence: 99%
“…The additional molecular changes that promote tumor progression, however, are not well characterized, but mutations in other oncogenes and tumor suppressor genes and altered cell signaling, cell cycle regulation, and apoptosis have been described in clinicopathologically aggressive thyroid neoplasms. 16,18,[20][21][22] As these changes have not been studied in the columnar cell variant of papillary thyroid carcinoma, we screened for mutations in BRAF and evaluated the immunophenotypic expression of the neoplasia-associated biomarkers b-catenin, cyclin D1, the cell proliferation marker Ki-67 (MIB-1), bcl-2, p53, estrogen receptor (ER), and progesterone receptor (PR) in nine cases of clinically aggressive and indolent columnar cell carcinomas.…”
mentioning
confidence: 99%